Exploratory study of the antecedents of psychological contract breach - Gallagher, Tom (Cranfield University, 2008)
This research presents a systematic review of literature focusing on the Human Resource Management concept of the Psychological Contract between an employee and their organisation. An initial overview of research on the broader topic is outlined to identify key themes in the field and to identify areas of research to be reviewed in greater detail. The major themes explored at this stage are the basic definition of the concept, the contents of the psychological contract, viewing the concept as a mental model or schema, the current methods used in existing research, how the agreement can be breached, the link to various employee outcomes and how the concept can be managed. The systematic review methodology is then set out to identify the causes or antecedents of breach, the differing ontological perspectives on the psychological contract concept and existing research which integrates the psychological contract with the related concept of employee engagement. 34 studies are examined and results are presented in the form of a narrative synthesis. Results suggest that the empirical evidence base of antecedents to breach is limited and that numerous potential antecedents to breach have not been fully tested due to limitations in existing research designs. Secondly, a new ontological perspective based on the Critical Realist perspective of Harré (2002) is proposed to develop existing work on the basic definition of the psychological contract concept. Finally, the lack of existing work which integrates both the psychological contract and employee engagement is highlighted with a recommendation for additional research on the ontology of the engagement concept.